Development and characterisation of dental composites containing anisotropic fluorapatite bundles and rods. Issue 8 (August 2020) - Altaie, Asmaa; Bubb, Nigel; Franklin, Paul; German, Matthew J.; Marie, Ali; Wood, David J.
Highlights: Composites with up to 40 wt% of fluorapatite could be made using dual asymmetric centrifugal mixing. At high filler loads, fluorapatite rods introduced additional toughening mechanisms. Degree of conversion was not changed by replacing glass for fluorapatite filler. Hardness and wear were not changed by replacing glass for fluorapatite filler. Under acidic challenge fluorapatite crystals dissolved releasing fluoride ions. Abstract: Objectives: To develop dental composites incorporating fluorapatite (FA) crystals as a secondary filler and to characterise degree of conversion, key mechanical properties and fluoride release. Methods: FA rod-like crystals and bundles were hydrothermally synthesised and characterised by scanning electron microscopy/energy dispersive X-ray spectroscopy (SEM/EDS), X-ray diffraction (XRD) and 19 F MAS-NMR. Composites were formulated containing BisGMA/TEGDMA/BisEMA and barium-aluminium-silicate glass (0FA). FA crystals were incorporated at 10 (10FA), 20 (20FA), 30 (30FA) and 40 wt% (40FA) maintaining a filler content of 80 wt% (63–67 vol%). Degree of conversion (DC), flexural strength (FS), flexural modulus (FM), fracture toughness ( K 1 C ), Vickers hardness (HV) and 2-body wear were measured. Fluoride release was measured in neutral and acidic buffers. Results: XRD and 19 F MAS-NMR confirmed that only FA was formed, whilst SEM revealed the presence of single rods and bundles of nano-rods. DC ranged between 56–60% ( p  > 0.05). FA composites showed lower FM and lower FS ( p  < 0.05), but comparable wear resistance and HV ( p  > 0.05) to 0FA. 30FA and 40FA showed similar K 1 C to 0FA ( p  > 0.05), with SEM showing evidence of toughening mechanisms, whereas 10FA and 20FA showed lower K 1 C ( p  < 0.05). FA containing composites released fluoride that was proportional to the amount of FA incorporated ( p  < 0.05) but only under acidic conditions. Significance: The addition of FA to the experimental composites reduced strength and stiffness but not the DC, hardness or wear rate. 30FA and 40FA had a higher K 1 C compared to other FA groups. Fluoride release occurred under an accelerated acidic regime, suggesting potential as a bioactive 'smart' composite.